THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY, GOOD CORPORATE GOVERNANCE, AND ENTERPRISE RISK MANAGEMENT ON FINANCIAL PERFORMANCE (Case Study on Consumer Non-Cyclicals Companies Listed on the Indonesia Stock Exchange for the 2021-2023 period) - Tiara Amaliyah Fitri; Agus Purwanto (Diponegoro Journal of Accounting, 2025)
This study aims to analyze the influence of Corporate Social Responsibility (CSR), Good Corporate Governance (GCG), and Enterprise Risk Management (ERM) on the financial performance of companies listed on the Indonesia Stock Exchange, specifically in the consumer non-cyclicals sector during the period of 2021 to 2023. Financial performance is measured using Return on Assets (ROA) as the main indicator. The research method employed is multiple linear regression analysis with secondary data obtained from the annual reports and sustainability reports of 40 selected companies.The results of the study indicate that CSR has a significant impact on financial performance, with a significance value of 0.034. Meanwhile, independent commissioners and the audit committee do not show a significant influence on financial performance, with significance values of 0.258 and 0.440, respectively. Additionally, the implementation of ERM does not have a significant effect on financial performance, with a significance value of 0.131.The conclusion of this study is that while CSR, GCG, and ERM are important aspects of corporate management, not all of these elements directly contribute to improving financial performance. This research provides insights for company management in formulating more effective strategies to enhance financial performance through better risk management and transparency in CSR practices.